Social change requires more justification than maintaining the status quo - Blanchar, John C.; Eidelman, Scott; Allen, Eric (Frontiers in Social Psychology, 2024)
Three studies demonstrate that, all else being equal, the threshold for justifying social change is higher than the threshold for maintaining the status quo. Higher standards for justifying change were observed across institutional requirements (Study 1), political candidates (Study 2), and city ordinances (Study 3). In all studies, lopsided standards increased as status quo preference increased. Study 1 revealed higher standards for novel entities lacking precedence, Study 2 demonstrated increased information-seeking about non-status quo alternatives to scrutinize them, and Study 3 showed biased interpretation of evidence toward maintaining the status quo, even when evidence skewed toward advocating change. The robustness of higher standards for change (d = 0.69; k = 7, N = 535), its relationship with status quo preference (r = 0.39; k = 7, N = 533), and information seeking scrutinizing alternatives (d = 1.17; k = 5, N = 285), rather than confirmation bias (d = 0.03; k = 5, N = 285), was established via small-scale meta-analyses including all data collected for this research program. Implications for theories of social change vs. status quo maintenance are discussed.